COMPARAÇÃO DA UTILIZAÇÃO DAS TÉCNICAS WATSU E RELAXAMENTO AQUÁTICO EM FLUTUAÇÃO ASSISTIDA NOS SINTOMAS DE ANSIEDADE, DEPRESSÃO E PERCEPÇÃO DA DOR - Acosta, Antonio Maria Cardozo (2010)
This study s purpose was to compare the effect of Watsu method and physical relaxing in swimming pools in the treatment of chronic pain. Another objective was to evaluate the symptoms of depression and anxiety as co-factors on these treatments. The sample was composed by 23 individuals of both genders above 18 years old. 13 individuals (12 females and 2 males) were treated with Watsu method and 10 were treated (07 females and 3 males) using assisted relaxing technique, picked up between patients suffering from chronic pain who looked for physiotherapy in the clinical centre UMESP s Physiotherapy School. The data were collected through structured interview. It was used associated scale to evaluate the pain perception, questionnaire for Beck depression symptoms evaluation, Idate-State Anxiety questionnaire and Idate-Trace Anxiety questionnaire. Due to the small size of the sample, the comparison between the two different treatments (Watsu and relaxing) and due to the fact that the results were equivalent in both procedures, only the results of parametric methods analysis will be presented (average t test, linear regression and variance analysis). Significant differences related to the levels of anxiety and depression before and after the treatment were not observed between the two groups. Related to pain perception, the comparison between the two groups showed that the both methods had a significant effect on pain reduction. This research suggests that the Watsu method was as efficacious as the relaxing method on pain control, however, the group of patients treated using Watsu method was composed by patients who showed higher initial levels of pain than the other group. Based on that, we can suppose that the clinical efficacy demand was higher for Watsu method. Another interesting finding was that the patients level of anxiety or depression apparently does not influence the response to the pain treatment. New controlled double-blinded studies are necessary to, beside of confirming the method efficacy, help to understand which Watsu technique procedure details are more efficacious for each type of pain and patient affective state.